Auditing in agricultural sales cooperatives and unions - SAIME ÃUNCE; NURCAN TURAN (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: This research examines how independent audit principles can help agricultural sales cooperatives in Turkey with their controlling issues. This research examines the potential contributions of an independent audit, which was implemented to ease the burden of auditing agricultural sales cooperatives and unions in Turkey.Method: This research relied on secondary sources of information such as existing literature reviews and relevant pieces of legislation. The Ministry of Commerce’s "communique on the determination of Agricultural Sales cooperative unions to be subject to independent audit," published in the Official Gazette on June 14, 2013, and data from the General Directorate of Artisans have both been used as sources for this article.Findings: Based on the findings of the SWOT analysis conducted within the context of this plan, the lack of effective and guiding existing internal and external audit mechanisms, as well as the negative experiences encountered by some types of cooperatives, are identified as weaknesses.Implications/Novel Contribution: An effective audit mechanism can be created with the help of these discussions and suggestions, which can influence the viewpoints of public officials tasked with and have the authority to formulate policies, particularly about the supervision of cooperatives. Not only that but suggestions for improving cooperative oversight are also offered.